Thermal Analysis and Heat Capacities of 1-Alkyl-3-methylimidazolium Ionic Liquids with NTf2-, TFO-, and DCA(-) Anions - Elena Goméz (2013)
Ionic liquids are good candidates as replacements for current heat-transfer liquids used in industry. For this use, it is important to know their thermal behavior. The melting, freezing, cold crystallization, and glass transition temperatures, together with heat capacities in the temperature range (293.15 to 333.15) K of the ionic liquids 1-alkyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide [C(n)MimNTf(2) (n = 2,3,4,6)], 1-hexyl-3-methylimidazolium trifluoromethanesulfonate (C(6)MimTFO), and 1-hexyl-3-methylimidazolium dicyanamide (C(6)MimDCA), have been determined using differential scanning calorimetry. Three different types of thermal behaviors were found, and in general it was concluded that as the temperature scan rate in the thermal analysis increases, the freezing temperature decreases, and the glass transition and cold crystallization temperatures increase. The heat capacity values of the imidazolium ionic liquids with the bis(trifluoromethylsulfonyl)imide anion increase as the alkyl-side chain of the cation increases, and the ionic liquid with this anion has higher heat capacities than their homologues with trifluoromethanesulfonate or dicyanamide as anions.